NONOSHIRI NO KOTOBA DALAM ANIME JUJUTSU KAISEN: KAJIAN KLASIFIKASI DAN BENTUK KATA UMPATAN BERDASARKAN TEORI WIJANA - M. Ridwansyah; Arza Aibonotika; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2026)
Nonoshiri no kotoba is an expressive speech act in the form of insults that often appears in Japanese conversation. The anime Jujutsu Kaisen contains many rude utterances, especially from antagonistic characters with high emotional intensity. This study aims to identify and describe the forms of insults in Jujutsu Kaisen based on I Dewa Putu Wijana’s classification theory. The research uses a qualitative descriptive method. Data were collected through listening and note-taking techniques from dialogues in season 1 and Shibuya Incident Arc. The results show 42 data of insults classified into 4 forms: basic words, affixed words, phrases, and sentences. Phrases and sentences are the most dominant forms, used to express contempt and threats. It is concluded that nonoshiri no kotoba in Jujutsu Kaisen reflects the arrogant and dominant character traits.